PREVALENCE OF GINGIVITIS AND PERIODONTITIS AMONG DIABETIC AND HYPERTENSIVE PATIENTS VISITING A UNIVERSITY DENTAL HOSPITAL - A RETROSPECTIVE ANALYSIS - Ilangovan, Swetha; Lochana Gajendran, Priya; Mani, Geo (International Journal of Psychosocial Rehabilitation, 2020)
Background: The most common risk factors of periodontal disease are diabetes and hypertension, which play a significant role in modulating the pathogenesis of periodontitis. Aim: The aim of the study is to find the prevalence of gingivitis and periodontitis among diabetic and hypertensive patients visiting a university dental hospital. Materials and Methods: This retrospective study was carried out by analyzing the case records of patients who visited Saveetha Dental College during a period between June 2019 and March 2020. The data included patients who had a history of diabetes and hypertension. Demographic details such as age, sex, marital status, occupation, address, and medical status were recorded. Periodontal parameters such as bleeding on probing, probing pocket depth, and loss of attachment were recorded to assess the periodontal status of the study population. The data was tabulated and entered in Excel, and the data was analyzed using Statistical Package for Social Sciences (SPSS) software; a chi-square test was done, and a p-value of 0.05 was set to be statistically significant. A nonparametric chi-square test was done for statistical analysis, and the variables compared were age, gender, gingivitis, and periodontitis among diabetic and hypertensive patients. Results: The total number of patients in the study was 2858 patients. Prevalence of gingivitis in diabetic patients was 52.85%, in hypertensive patients was 27.85%, and in both diabetes and hypertension was 19.3%. The prevalence of periodontitis in diabetics was 53.84%, in hypertensives was 24.37%, and in patients with both diabetes and hypertension was 21.72%. There was higher male predilection among the diabetic and hypertensive patients. The mean age group of gingivitis and periodontitis in diabetic and hypertensive patients was 53.38±10.97 years. Conclusion: Within the limitations of the study, we found male predilection among both diabetic and hypertensive patients. Gingivitis and periodontitis were more common in the age group of 46-60 years. Among diabetic patients, 41.26% had gingivitis and 58.74% had periodontitis. There was a higher prevalence of periodontitis (55.07%) than gingivitis (44.93%) in the hypertensive group. Similarly, among the patients who had both diabetes and hypertension , there was a higher prevalence of periodontitis (61.15%) than gingivitis (38.85%).